Trademark Dispute Resolution in Indonesia: Case Study of the Dispute between the Trademarks "Pure Kids" and "Pure Baby" - Vena Salsabilla (Proceeding International Conference Restructuring and Transforming Law, 2023)
Brands can result in unhealthy trade competition because similar products can be distinguished by their origin, quality and guarantee that the product is original. So efforts to provide protection for brand rights are only given to business actors or companies whose brands already existter.For brands that are already available after and proven to imitate or plagiarize brands that have already been established Therefore, there will be an opinion regarding sanctions for cancellation and deletion of the brand in accordance with Article 76 to Article 79 of Law Number 20 of 2016. The problem in this research is that there are similarities in essence or overall in the Pure Kids brand and the Pure Baby brand which results in losses for one of the parties. This research will also discuss brand protection in Indonesia.Researcherthis is using normative juridical research methods which means that in this research it refers to legal norms contained in statutory regulations. The resolution of the trademark problem between the Pure Kids brand and the Pure Baby brand can be done by filing a lawsuit with the Commercial Court in accordance with Article 83 of Law Number 20 of 2016. The results of this research show that the Brand pricing in Indonesia is by system first tofileas well as the Regional Applicant Brands must act in good faith. In the dispute over the Pure Kids brand with Pure Baby, the judge granted the Plaintiff's lawsuit because the Plaintiff's brand was already establishedyesftaras well as the Defendant's brand oundanmany similarities with the Plaintiff's trademark.